PENGARUH VARIASI WAKTU PENGUKUSAN DAN SUHU PENGERINGANTERHADAP KARAKTERISTIK TEPUNG MAGGOT BLACK SOLDIER FLY - Elida Novita; Dian Purbasari; Leni Putrianggraini; Bambang Herry Purnomo (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
BSF maggot flour is one of the alternative protein source feed ingredients that can be applied to quail farms. With the potential for high protein content, proper handling so that the nutrients in the ingredients are maintained needs to be known. The purpose of this study was to determine the effect of variations in the treatment of steaming time and drying temperature on the characteristics of BSF maggot flour and to determine the best treatment in the processing of BSF maggot flour as protein source of quail feed. The experimental design used was a completely randomized design (CRD) with two factors. The first factor is the steaming time (10, 20, and 30 minutes). The second factor is the drying temperature (60, 70, and 80°C). The observed variables were color, water absorption, water content, protein, and fat. The methods used are: measurement of color (Soewarno), water absorption (Fardiaz methode), moisture content (thermogravimetry), protein (Kjeldahl), and fat (soxhlet). The data obtained were analyzed by means of variance (ANOVA), the results of the analysis which showed the average difference were followed by Duncan's test. The results of statistical analysis showed that the steaming time had an effect on the absorption of water and protein. While the drying temperature affects the value of L (brightness), water absorption, and protein. Based on the SNI standard for quail feed, the fat content in each sample exceeded the maximum limit. So that BSF maggot flour with this treatment is not recommended to be given to quail.